Assessing therapeutic decisions in generalized myasthenia gravis: Study protocol - Gerardo Gutiérrez-Gutiérrez; Rocío Gómez-Ballesteros; Javier Sotoca; Adrián Ares; Ramón Villaverde; Virginia Reyes; Thaís Armangué; Elisa Salas; Paola Díaz-Abós; Pablo Rebollo; Mónica Sarmiento; Iratxe Escobar; et al. (PLoS ONE, 2025)
Background The therapeutic landscape in generalized myasthenia gravis (gMG) has been continuously evolving in recent years, with over five products approved, each with different efficacy, safety, and administration profiles. With the availability of new targeted treatments, physicians are faced with the challenge of therapeutic decision-making tailored to traditional therapeutic goals, individual preferences, and personal experience, seeking optimal disease control with a positive safety profile. In this context of uncertainty and multiple novel choices, this study aims to provide insights into the preferred treatment choices of neurologists managing gMG and to identify demographic, professional or behavioral factors influencing the decision-making process. Methods This is a non-interventional, cross-sectional, web-based study involving 150 neurologists treating gMG patients in collaboration with the Spanish Society of Neurology. The primary endpoint will be to assess preferences for different gMG treatment attributes using a conjoint analysis to create hypothetical treatment scenarios. Therapeutic inertia, described as the lack of treatment initiation or intensification when therapeutic goals are not met, will be evaluated as a secondary endpoint through 7 case scenarios simulating real gMG clinical practice situations. Neurologists will also answer a survey composed of demographic, professional, and behavioral characteristics (user resistance behavior, care-related regret, burnout, risk attitude, empathy, work fulfilment, and personality traits) to recognize possible factors influencing decisions. Conclusions The study findings will contribute to better understanding of decision-making in gMG under a changing therapeutic landscape with multiple new targeted options, and will identify which factors have a role in affecting those decisions.